Translational regulation of PKD1 by evolutionarily conserved upstream open reading frames - Lei Chen; Xia Gao; Xiangshen Liu; Ye Zhu; Dong Wang (RNA Biology)
Mutations in PKD1 coding sequence and abnormal PKD1 expression levels contribute to the development of autosomal-dominant polycystic kidney disease, the most common genetic disorder. Regulation of PKD1 expression by factors located in the promoter and 3´ UTR have been extensively studied. Less is known about its regulation by 5´ UTR elements. In this study, we investigated the effects of uORFs and uORF-affecting variants by combining bioinformatic analyses, luciferase reporter assays, RT-qPCR and immunoblotting experiments. Our analyses demonstrate that PKD1 mRNA contains two evolutionarily conserved translation-inhibitory uORFs. uORF1 is translatable, and uORF2 is likely not translatable. The 5´ UTR and uORFs do not modulate downstream protein output under endoplasmic reticulum stress and oxidative stress conditions. Some of uORF-perturbing variants in the SNP database are predicted to affect gene translation. Luciferase reporter assays and RT-qPCR results reveal that rs2092942382 and rs1596636969 increase, while rs2092942900 decreases main gene translation without affecting transcription. Antisense oligos targeting the uORFs reduce luciferase protein levels without altering luciferase mRNA levels. Our results establish PKD1 as a novel target of uORF-mediated translational regulation and mutations that perturb uORFs may dysregulate PKD1 protein level.